The Strategy of Ali Musri Semjan Putra in the Management of Bermanhaj Salaf Islamic Educational Institutions - Kardina Engelina Siregar; Ali Musri Semjan Putra (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The management strategy of Islamic educational institutions is something that must be owned by every Islamic educational institution, this aims to plan, advance, control, and evaluate the vision and mission of the institution. Islamic educational institutions must be able to build a generation of Muslims who are strong, master science, technology and have noble character. To achieve this goal, Islamic educational institutions must be optimally managed with relevant strategies. Islamic educational institutions with the salaf manhaj are currently growing rapidly and are in great demand by the public, of course this is interesting to discuss. Manhaj salaf refers to the fundamental principles of Islam, namely the Qur'an and Sunnah, the traditions of the Prophet and the Salafush Salih with jargon returning to the Qur'an and ash-Sunnah in accordance with the understanding of friends and tabi'in circles. One form of implementation of salafiyah da'wah in society is the existence of Islamic educational institutions that have the salaf manhaj, so that students get Islamic knowledge and culture in accordance with the salaf manhaj. Ali Musri Semjan Putra is someone who has the competence, knowledge and experience in pioneering, establishing and managing Islamic educational institutions with manhaj salaf. There are several Salaf-based Islamic educational institutions under his guidance, namely: Imam Syafii Islamic Boarding School (STDIIS) Jember, Dar el-Iman Padang Foundation, West An-Najiya Foundation, Makassar Ibnul Qoyyim Foundation, Yogyakarta Ar-Raudhoh Foundation, The Imam Syafii Genteng Banyuwangi Foundation, the Fathul Barry Indonesia Foundation, the Imam Asy Syafii Pekanbaru Scholars Foundation. The strategy implemented by him provided change and progress for these Islamic educational institutions, so that they could develop, advance da'wah and Islamic law, assist government programs in terms of education, namely educating the life of the nation and forming human beings with character. This research is a character study with a type of descriptive qualitative field research. The Salaf-based Islamic Education Institutions studied focused only on the Scholars Foundation of Imam Asy Syafii Pekanbaru. The results of this study describe the relevant and visionary strategy of Ali Musri Semjan Putra in managing Islamic educational institutions with the Salaf manhaj.